Mechanical properties and flammability analysis of wood fiber filled polylactic acid (PLA) composites using additive manufacturing - Siddiqui, Vasi Uddin; Yusuf, J.; Sapuan, S.M.; Hasan, Mohammad Zaid; Mudah Bistari, Muhammad Muawwidzah; Mohammadsalih, Zaid G. (Taylor and Francis Ltd., 2024)
Natural fibers, such as wood fibers, can substitute for synthetic fibers in various applications due to their low environmental impact, cost-effectiveness, and outstanding mechanical properties as rapid-growing materials and renewable resources. This paper aims to investigate the mechanical properties of 20% wood fiber as a reinforcement material in polylactic acid (PLA) using an additive manufacturing approach. The samples were fabricated using 3D printing techniques. The relevant parameters included the orientation of printing in X, Y, and Z directions, with the percentage of infill set to be 100%. The findings indicated that bio-composites and their adopted printing orientations confirmed the significant effects on the mechanical properties. Pure PLA possessed superior properties in all directions compared to wood/PLA. The highest values were 50.33 MPa for tensile strength and 94.36 MPa for flexural strength, both achieved in Y orientations. However, composites showed an improvement in tensile and flexural moduli in X orientation with 1395.40 MPa, and 2937.72 MPa for Young and flexural modulus, respectively. In the flammability test, wood/PLA bio-composites were ignited easily with reduced smoke production compared to the neat PLA. Wood/PLA bio-composites exhibited high stiffness, and their mechanical properties were influenced by many factors, such as percentage of weight fraction, wood type, and printing orientations.